Nursing Skills Impact Patient Anxiety Levels in Emergency Unit - Riyan Dwi Prasetyawan (LPPM Universitas Harapan Bangsa, 2026)
Anxiety within a family, especially for families with hospitalized members, is a form of emotional needs disruption due to inadequate fulfillment. This study examines the association between nurses' skills and patient anxiety levels in the Emergency Unit of Wuluhan Health Center in 2024. The research employs a cross-sectional design. A total of 55 respondents who visited the Emergency Unit of Wuluhan Health Center between September and November 2024 were included as study subjects. This study identifies the independent variable as the nursing skills in the Emergency Unit of Wuluhan Health Center, and the dependent variable is the anxiety level of patients in the same unit. Participants were chosen through purposive sampling. The study applies the Rank Spearman analysis. The research findings show a p-value of 0.000 < α (0.05), Establishing a significant connection between nursing skills and patient anxiety outcomes in the Emergency Unit of Wuluhan Health Center. By improving nurses' skills and their relationship with patients, anxiety levels can be reduced to a lower degree. This study contributes to the existing literature by highlighting the specific correlation between nurses' technical and interpersonal skills and patients' anxiety levels in a primary care emergency setting. Unlike previous studies, this research focuses on a primary health center, providing insights into frontline nursing practices in under-resourced emergency units.